PRAXIS OF COMPETITIVE POSITIONING AND ORGANIZATIONAL STRATEGIC GROUP DYNAMICS IN NIGERIAN TELECOMMUNICATION SECTOR - Iyamabhor, Martins; Agbeche, Aaaron Oghenevwayere; Iyamabhor, Onome Precious (Kashere Journal of Management Sciences, 2025)
This study investigated the praxis of competitive positioning and organizational strategic group dynamics at MTN Telecommunications in Asaba, Delta State. The specific objectives are to determine the extent to which resource availability and research development contribute to the praxis of competitive positioning and organizational strategic group dynamics at MTN Telecommunications in Asaba, Delta State. Survey research design was adopted in the study, with a population of 193 which consists of all customers of MTN Telecommunications in Asaba, Delta State. Using a 12-item validated structured questionnaire administered to 130 staff members and customers of MTN in Asaba, Delta State, Of the 130 questionnaires distributed, 125 (96.2%) were returned and five were rejected. The analytical tools employed included correlation and multiple regression analysis. The study found out, that resource availability and research development positively impacts the strategic group dynamics within MTN Telecommunications sector, Integrating expertise and capabilities from various organizations enhances product performance, and combining financial resources with strategic alliances further improves product performance. However, strategic resources, which are often intangible, are neither easily identifiable nor quickly developed. Therefore, the researcher recommends that telecommunications management should focus on improving resource availability to boost organizational performance.